Applications of magnetic materials separation in biological nanomedicine. Issue 16 (27th February 2019) - Ma, Yuanyuan; Chen, Tianxiang; Iqbal, Muhammad Zubair; Yang, Fang; Hampp, Norbert; Wu, Aiguo; Luo, Liqiang
Abstract: As a result of their advantages for superparamagnetic properties, good biocompatibility, and high binding capacity, functionalized magnetic materials became widely popular over the past couple of decades, being applied on large scale in various processes of sample preparation for biomedicine. In this work, we perform an in‐depth review on the current progress in the field of magnetic bead separation, discussing in detail the physical basis of this process, various synthesis methods and surface modification strategies. We place special focus of attention as well on the latest applications of magnetic polymer microspheres in cell separation, protein purification, immobilized enzyme, nucleic acid separation, and extraction of bioactive compounds with low molecular weight. Existing problems are highlighted and possible trends of magnetic separation techniques for biomedicine in the future are proposed.